Adaptive Management Tools: Concept Notes System - Mercy Corps (Mercy Corps, 2015)
Mercy Corps finds adaptive management is supported by four different but interconnected elements: Culture, People & Skills, Tools & Systems, and Enabling Environment. These elements are discussed in the context of one of Mercy Corps’ complex programmes in pastoral Ethiopia.

Learning to Adapt: Exploring Knowledge, Information and Data for Adaptive Programmes and Policies - Workshop Summary Report - fhi360 (IDS, 2015)
Adaptive management is increasingly seen as critical capability for development programmes and policies that are more effective, efficient, relevant and sustainable. There is increasing recognition that such work requires significant changes to the organizational structures, management processes, accountability and performance cultures and indivi

Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice